On Micropolar Fluid Model for Blood Flow Through an Artery with Mild Stenosis - Dey, K.N.; Mazumdar, H.P. (Engineering Transactions, 1995)
Blood flow through an artery with various shapes of mild constrictions has been analysed by characterising it as a micropolar fluid. Microsfructural effects on the pressure gradient, resistance to the flow and the wall shear stress are determined. The results are numerically computed and discussed.